Preverjanje sporazumevalne zmožnosti v slovenskem jeziku na splošni maturi od začetkov do danes - Bavdek, Mojca (Jezik in slovstvo, 2015)
The article provides a concise review of the verification and evaluation of pupils' Slovenian language proficiency in the general secondary school leaving examination (the so-called Matura). It lists the team of authors who planned and designed the Slovenian language examination, as well as presenting the examination structure, the Second Examination Paper intended for the linguistic analysis of a non-fiction text, and the requirements that such a text should meet. The article also discusses the method of evaluation and assessment of the Examination Paper and the oral part of the examination, as well as presenting the examination catalogue and seminars for teachers involved in the implementation of the General Matura Examination.
Keywords: Slovene; slovenščina; splošna matura; preverjanje znanja; izpitne pole; izpitni katalogi; 1992-2015